2005
DOI: 10.1111/j.1365-246x.2005.02782.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Jurassic-Early Cretaceous closure of the Mongol-Okhotsk Ocean demonstrated by new Mesozoic palaeomagnetic results from the Trans-Baïkal area (SE Siberia)

Abstract: S U M M A R YWe present new palaeomagnetic results from the Transbaïkal area (SE Siberia), from the Mongol-Okhotsk suture zone, the boundary between the Amuria and Siberia blocks. In order to better constrain the time of closure of the Mongol-Okhotsk Ocean in the Mesozoic, we collected 532 rock samples at 68 sites in six localities of basalts, trachy-basalts and andesites, from both sides of the Mongol-Okhotsk suture: at Unda river (northern side. Progressive thermal demagnetization enabled us to resolve low (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
164
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(189 citation statements)
references
References 32 publications
17
164
0
Order By: Relevance
“…Systematic magmatic, paleobiogeographical and paleomagnetic studies have confirmed that the Mongol-Okhotsk ocean closed in a scissor-like movement from the late Carboniferous-Permian in central Mongolia, to Triassicearly Jurassic in northeastern Mongolia (Sengör et al 1993b;Zorin 1999;Kravchinsky et al 2002;Cogné et al 2005;Tomurtogoo et al 2005), after the final stage of the northward or both northward and southward subduction of the Mongol-Okhotsk ocean and the amalgamation of the Siberia block and the combined Mongol-North China block in the late Jurassic, the compressional setting transformed into extensional due to the gravitational collapse of orogenically thickened crust and upwelling of asthenosphere, then the combined effect of heating of the asthenosphere and the decompression of the lithospheric extension will result in the partial melting of the lithospheric mantle which had been previously metasomatized during the multi-stage collisions of continent-arc and continent-continent in the course of the evolution of Paleo-Asian Ocean.…”
Section: Geodynamic Implicationsmentioning
confidence: 83%
“…Systematic magmatic, paleobiogeographical and paleomagnetic studies have confirmed that the Mongol-Okhotsk ocean closed in a scissor-like movement from the late Carboniferous-Permian in central Mongolia, to Triassicearly Jurassic in northeastern Mongolia (Sengör et al 1993b;Zorin 1999;Kravchinsky et al 2002;Cogné et al 2005;Tomurtogoo et al 2005), after the final stage of the northward or both northward and southward subduction of the Mongol-Okhotsk ocean and the amalgamation of the Siberia block and the combined Mongol-North China block in the late Jurassic, the compressional setting transformed into extensional due to the gravitational collapse of orogenically thickened crust and upwelling of asthenosphere, then the combined effect of heating of the asthenosphere and the decompression of the lithospheric extension will result in the partial melting of the lithospheric mantle which had been previously metasomatized during the multi-stage collisions of continent-arc and continent-continent in the course of the evolution of Paleo-Asian Ocean.…”
Section: Geodynamic Implicationsmentioning
confidence: 83%
“…Jolivet et al, 2010Jolivet et al, , 2013aJolivet et al, , 2013bMetelkin et al, 2010;Wilhem et al, 2012 and references therein). In the southern Altai Mountains, several AFT studies point to a Late Jurassic-Cretaceous basement cooling event, which is generally linked to both the Mongol-Okhotsk and the Cimmerian Orogeny during the Mesozoic (Cogné et al, 2005;De Grave et al, 2007Glorie et al, 2012aGlorie et al, , 2012bHalim et al, 1998;Yuan et al, 2006). However, most authors favor the Mongol-Okhotsk Orogeny and subsequent collapse as the main driving force for the Late Jurassic-Cretaceous cooling and denudation in the Altai, given the more proximal location of the Altai to the Mongol-Okhotsk collision zone.…”
Section: Late Mesozoic Reactivationmentioning
confidence: 96%
“…This orogen is attributed to the closure of the Mongol-Okhosk Ocean from central Mongolia to the Okhotsk Sea to the east. It is widely accepted that this ocean closed with a scissor-like motion, with a pin point located in central Mongolia (Zonenshain et al 1990;Sengör and Natal'in 1996;Kravchinsky et al 2002;Cogné et al 2005;Tomurtogoo et al 2005). The age of ocean closure remains controversial, from early-middle Jurassic (Zorin 1999) to late Jurassic-early Cretaceous (Kravchinsky et al 2002;Cogné et al 2005).…”
Section: Regional Tectonic Settingmentioning
confidence: 96%